Adaptive techniques for dynamic processor optimization : theory and practice - Wang, Alice, 1975-; Naffziger, Samuel (New York : Springer, 2008)
Adaptive Techniques for Dynamic Processor Optimization: Theory and Practice collects in one place, the research and experience of pioneers in the burgeoning area of dynamically adaptive silicon, where the part optimizes itself "on the fly". Static and potentially unique configuration of each manufactured part has been practiced for some time, but advanced silicon processes no longer allow high performance parts that luxury. Variations, environmental conditions and diverse operating modes all confer a great competitive advantage on chips that succeed at monitoring conditions and adapting their operating point to optimize speed, power and reliability. This book discusses the different approaches and responses to adaptive techniques used for processor power, frequency and functionality optimization. Adaptive Techniques for Dynamic Processor Optimization: Theory and Practice includes chapter contributions that explore promising approaches and present the supporting data. This book is written for engineers interested in adaptive techniques for processors
Technology Challenges Motivating Adaptive Techniques -- Technological Boundaries of Voltage and Frequency Scaling for Power Performance Tuning -- Adaptive Circuit Technique for Managing Power Consumption -- Dynamic Adaptation Using Body Bias, Supply Voltage, and Frequency -- Adaptive Supply Voltage Delivery for Ultra -- Dynamic Voltage Scaled Systems -- Dynamic Voltage Scaling with the XScale Embedded Microprocessor -- Sensors for Critical Path Monitoring -- Architectural Techniques for Adaptive Computing -- Variability -- Aware Frequency Scaling in Multi -- Clock Processors -- Temporal Adaptation -- Asynchronicity in Processor Design -- Dynamic and Adaptive Techniques in SRAM Design -- The Challenges of Testing Adaptive Designs
1
Keywords: Microprocessor